Die vestiging van die Kerk in Natal, die Vrystaat en Transvaal na afloop van die Groot Trek - Storm, J. M. G. (1987)
The settlement of the Church in Natal, the Free Stale and Transvaal after the Great Trek After settling in the Orange Free State, Natal and Transvaal, the Voortrekkers established congregations in Port Natal, Pietermaritzburg, Wenen, Winburg and Potchefstroom. The House of Assembly appointed an Americal missionary, Daniel Lindley, as minister of the Voortrekkers. After the annexation by England of Natal and Orange Free State, the congregations in these areas were incorporated in the Dutch Reformed Church of the Cape Colony. The Cape Synod admitted these congregations to the Church district of Transgariep. The congregation in Transvaal was the only congregation that was left of the Voortrekkerkerk.
Keywords: Sociology and Ethics; Ancient Semitic and Classical Languages; Philosophy; Aspects of Religious Studies; Practical Theology; Ministers of Religion; Scholars; Philosophers; Theologians; Netherdutch Reformed Church; Theology